Distribusi Pendapatan dan Kemiskinan di Indonesia dalam Perspektif Ekonomi Islam: Tantangan dan Prospek Masa Depan - Syahputra, Angga; Harahap, Isnaini; M. Nawawi, Zuhrinal; Kaswinata, Kaswinata (Jurnal Iqtisaduna, 2023)
This research examines income distribution and poverty in Indonesia through the lens of Islamic economics. By focusing on the principles of inclusiveness, fairness, and sustainability in Islamic economics, this research goes in-depth on economic inequality and poverty in Indonesia through a descriptive qualitative approach. The findings show that despite a decline in poverty, income inequality in Indonesia is still high, creating a widening gap between the rich and poor. In-depth analysis reveals the important role of Islamic economics, zakat, infaq, and Islamic financial institutions in addressing inequality and poverty. The research also examines the challenges in implementing Islamic economic principles and presents innovative strategies to improve income distribution. The focus on zakat and infaq as potential redistribution instruments highlights the need for a more structured and sustainable approach. This research provides a foundation for inclusive and equitable policies, guiding Indonesia's steps towards equitable and sustainable economic growth. By integrating Islamic economic principles, this research suggests ways to create a more just and prosperous society, in accordance with Islamic principles and global sustainable development principles.